Mapping a Novel Black Spot Resistance Locus in the Climbing Rose Brite Eyes™ (‘RADbrite’) - Zurn, Jason D.; Zlesak, David C.; Holen, Matthew; Bradeen, James M.; Hokanson, Stan C.; Bassil, Nahla V. (Frontiers in Plant Science, 2018)
Rose black spot, caused by Diplocarpon rosae, is one of the most devastating foliar diseases of cultivated roses (Rosa spp.). The globally distributed pathogen has the potential to cause large economic losses in the outdoor cultivation of roses. Fungicides are the primary method to manage the disease, but are often viewed unfavorably by home gardeners due to potential environmental and health impacts. As such, rose cultivars with genetic resistance to black spot are highly desired. The tetraploid climbing rose Brite EyesTM (‘RADbrite’) is known for its resistance to black spot. To better characterize the resistance present in Brite EyesTM, phenotyping was conducted on a 94 individual F1 population developed by crossing Brite EyesTM to the susceptible tetraploid rose ‘Morden Blush’. Brite EyesTM was resistant to all D. rosae races evaluated except for race 12. The progeny were either resistant or susceptible to all races (2, 3, 8, 9, 10, 11, and 13) evaluated. The segregation ratio was 1:1 (χ2 = 0.3830, P = 0.5360) suggesting resistance is conferred by a single locus. The roses were genotyped with the WagRhSNP 68K Axiom array and the ‘polymapR’ package was used to construct a map. A single resistance locus (Rdr4) was identified on the long arm of chromosome 5 homoeolog 4. Three resistance loci have been previously identified (Rdr1, Rdr2, and Rdr3). Both Rdr1 and Rdr2 are located on a chromosome 1 homoeolog. The chromosomal location of Rdr3 is unknown, however, races 3 and 9 are virulent on Rdr3. Rdr4 is either a novel gene or an allele of Rdr3 as it provides resistance to races 3 and 9. Due to its broad resistance, Rdr4 is an excellent gene to introgress into new rose cultivars.